Exploring the Interplay of Institutional Excellence, Artificial Intelligence and Crisis Management: A Qualitative Case Study of the United Arab Emirates (UAE) Department of Passports and Immigration, 2023-2024 - Alyassi, Ismail Mohamed Abdellatif Ahmed; Mohamad, Siti Syuhadah (Journal of Posthumanism, 2025)
This qualitative case study examines how institutional excellence, artificial intelligence integration, and crisis management interact within the UAE Department of Passports and Immigration during 2023-2024. Using triangulated data collection including 15 semi-structured interviews, participant observations, and analysis of 127 organizational documents, the research reveals how AI integration fundamentally transforms government operations in complex immigration environments. Findings demonstrate that AI redefined institutional excellence beyond traditional efficiency measures, achieving 45% increases in processing volume while improving customer satisfaction from 73% to 91%. Crisis management requirements accelerated AI adoption by two years, with AI-human collaboration creating synergistic capabilities exceeding individual component contributions. The study contributes to institutional theory by showing simultaneous adaptation across regulatory, normative, and cultural-cognitive elements during AI transformation, while providing practical guidance for government agencies pursuing digital transformation in diverse operational contexts.